William E. Miller, Revised and Annotated Code of Iowa, Containing All the Statutes of the State of Iowa of a General Nature in Force July 4, 1880, Being the Code of 1873 as Amended by Statutes Passed by the Fifteenth, Sixteenth, Seventeenth and Eighteenth General Assemblies, and All the General and Permanent Statutes of those Sessions Suitably Arranged...Authorized and Made Legal Evidence by Chap. 196, Laws of 1800, vol. 1 (Des Moines, IA: Mills & Company, 1880), 265. Title 8, Ch. 1, § 36 Unlawful for Other than Regularly Organized Militia to Organize. Undated - (:unkn) unknown (General Publisher, 1880)
Prohibited any body of men, other than the regularly organized volunteer militia and federal troops, from associating as a military company or to drill or parade.
--
Keywords: MILITIAS